Indirect Measurements of n- and p-Induced Reactions of Astrophysical Interest on Oxygen Isotopes - Sergi, M. L.; Guardo, G. L.; La Cognata, M.; Gulino, M.; Mrazek, J.; Palmerini, S.; Spitaleri, C.; Wiescher, M. (Frontiers in Astronomy and Space Sciences, 2020)
Observations of abundances and isotopic ratio determinations in stars yield powerful constraints on stellar models. In particular, the oxygen isotopic ratios are of particular interest because they are affected not only by nucleosynthesis but also by mixing processes. This review is focused on the measurements via the Trojan Horse Method (THM) that have been carried out to investigate the low-energy cross sections of proton and neutron-induced reactions on 17O as well as the proton-induced reaction on 18O, overcoming extrapolation procedures and enhancement effects due to electron screening. The (p,a) reactions induced on these oxygen isotopes are of paramount importance for the nucleosynthesis in many stellar sites, including red giants (RGs), asymptotic giant branch (AGB) stars, massive stars, and classical novae. The indirect measurement of the 17O(p,a)14N reaction was performed. The strength of the narrow resonance at 65 keV was evaluated and it was used to renormalize the corresponding resonance strength in the 17O+p radiative capture channel. The reaction rate was evaluated for both the 17O(p,a)14N and the 17O(p,g)18F, and a significant difference of 30% and 20% with respect to the literature was found in the temperature range relevant for RG, AGB and massive stars nucleosynthesis. Regarding the 18O(p,a)15N reaction, the strength of the 20 keV resonance was extracted, which is the main contribution to the reaction rate for astrophysics. This approach allowed us to improve the data accuracy of a factor 8.5, as it is based on the measured strength instead of extrapolations or spectroscopic measurements. Finally, the 17O(n,a)14C reaction was studied because of its role during the s-process nucleosynthesis as a possible neutron poison. This study represents the extension of THM to resonant neutron-induced reactions. In this measurement, the subthreshold level centered at -7 keV in the center-of-mass, corresponding to the 8.039 MeV 18O excited level, was observed. Moreover, the THM measurements showed a clear agreement with the available direct measurements because of the additional contribution of the 8.121 MeV 18O level, strongly suppressed in direct measurements because of its l=3 angular momentum. The contributions to the total reaction rate were than evaluated for future astrophysical applications.